An assessment of oxidative potential of indoor/outdoor airborne particulate matter at roadside and urban background sites in London - Mohd Aris, Mohd Shukri; Kelly, Frank; Barratt, Benjamin (2015)
INTRODUCTION: People spend most of their time indoors, in buildings such as schools and offices, as well as their homes. Recent interest in Indoor Air Quality (IAQ) suggests that the contribution of outdoor pollutants and indoor airborne particulate may be responsible for the aggregation of a number of respiratory illnesses. Because of these health implications, it is important to understand the characteristics of airborne particulate matter inside/outside (I/O) the building and the variables affecting the degree of exposure to them. Thus, this study aims to establish spatial and temporal descriptive analysis of the indoor-outdoor PM OP long term dataset. The relationship between ascorbate (OPAA), glutathione (OPGSH) and building occupancy are used to create a basic characterisation of the metrics. METHODS: Indoor and outdoor PM total suspended particle (PMTSP) samples were collected from two contrasting sites in London using OSIRIS monitor. PM oxidative activity was examined by quantifying its capacity to deplete antioxidants from the synthetic respiratory tract lining fluid (RTLF) model. RESULTS: The novel time series of PM OP dataset established in this study highlighted a clear difference between the two sites. Indoor OP metrics in the roadside building recorded higher depletion rates compared to the urban background site. At urban background site, when indoor OP dataset were categorised and group as building occupancy and seasonal dependent, the indoor PM OP antioxidants metrics was found to have a higher depletion rate during occupied period and was observed during winter time, which particularly in particulate mass metric. At roadside site, interestingly, a significant decrease in PM-induced antioxidant depletion indoors, observed after the door upgrade. CONCLUSIONS: This study demonstrated that oxidative activity in the context of particulate metrics, from both internal and external sources, is a useful tool to illustrate any source changes in the transfer of pollutants into buildings. The two sites showed a clear difference in PM TSP OP antioxidants metrics, particularly the indoor OP metrics in the roadside building. This may explain the high reactive PM composition attributed from outdoor vehicle combustion.